2015
DOI: 10.1007/s11224-015-0658-9
|View full text |Cite
|
Sign up to set email alerts
|

Accurate modeling of cation–π interactions in enzymes: a case study on the CDPCho:phosphocholine cytidylyltransferase complex

Abstract: ABSTRACT:Cation- interactions are functionally relevant, strong secondary interactions that play versatile roles in a variety of chemical and biological systems. Therefore it is very important to be able to describe accurately and reliably these interactions. In this study we propose a methodology for the accurate modelling of cation- interactions in proteins using QM/MM calculations. We developed a methodology for computing the many-body interaction energy terms and tested the effect of various factors on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…18 Since the discovering of this interaction many theoretical approaches explaining its physical origin have been devised. 19 The interaction of the cation with the large, permanent quadrupole moment of aromatic rings was initially established as the driving force of the cation-π interaction. 20,21,22 Other investigations revealed that repulsion and induction contributions are important too.…”
Section: Introductionmentioning
confidence: 99%
“…18 Since the discovering of this interaction many theoretical approaches explaining its physical origin have been devised. 19 The interaction of the cation with the large, permanent quadrupole moment of aromatic rings was initially established as the driving force of the cation-π interaction. 20,21,22 Other investigations revealed that repulsion and induction contributions are important too.…”
Section: Introductionmentioning
confidence: 99%